Exploring Lifestyles and Sensory Processing Patterns of Toddlers in Relation to Sleep Patterns Using Body Movement Analysis - Azusa Ono; Yoshiko Iwatani; Arika Yoshizaki; Tomoko Nishimura; Ikuko Mohri; Kuriko Kagitani-Shimono; Masako Taniike (Clocks & Sleep, 2025)
This study explored the impact of lifestyle habits and sensory processing patterns on sleep quality by analyzing body movements (BMs) during the first and last 3 h of sleep in toddlers. We collected cross-sectional data about sleep-related habits from 58 toddlers using a mobile application. Actigraphy measured BMs during nighttime sleep and 1 h before bedtime, as well as sleep latency, over 8 consecutive days. The Infant/Toddler Sensory Profile was used to assess the toddlers’ sensory processing patterns. The participants had a mean age of 22.0 ± 2.0 months. BMs were significantly lower during the first 3 h of sleep. Longer sleep latency was significantly associated with media use and higher activity levels before bedtime. Ending a nap earlier and consuming a substantial breakfast were correlated with lower BMs during the first 3 h of sleep. Auditory and oral sensory scores were positively correlated with BMs during the first 3 h of sleep. However, no specific factors related to lifestyle habits or sensory processing patterns were found to correlate with BMs during the last 3 h of sleep. Lifestyle habits and sensory processing patterns have a significant impact on toddlers’ sleep quality, emphasizing the importance of appropriate routines and environments.